Peralkaline Felsic Magmatism of the Atlantic Islands - Jeffery, Adam J.; Gertisser, Ralf (Frontiers in Earth Science, 2018)
The oceanic-island magmatic systems of the Atlantic Ocean exhibit significant diversity in their respective sizes, ages, and the compositional ranges of the magmas they have produced. Nevertheless, almost all of the major Atlantic islands and island groups have produced peralkaline felsic magmas, implying that similar petrogenetic regimes may be operating throughout the Atlantic Ocean, and elsewhere. The origins of peralkaline magmas are frequently linked to low-degree partial melting of enriched mantle, followed by protracted differentiation in the shallow crust. Nevertheless, additional petrogenetic processes such as magma mixing, crustal melting, and contamination have been identified at numerous peralkaline centres. The onset of peralkalinity leads to magma viscosities lower than those typical for metaluminous felsic magmas, which has profound implications for processes such as crystal settling. A literature compilation demonstrates trends which suggest that the peralkaline magmas of the Atlantic Ocean islands are generated primarily via extended (up to ~ 95 %), open system fractional crystallisation of mantle-derived mafic magmas. Crustal assimilation is likely to become more significant as the system matures and low-solidus material accumulates in the crust. Magma mixing occurs between mafic and felsic end-members, and also between variably-evolved felsic magmas, and is often recognised via hybridised intermediate magmas. The peralkaline magmas are hydrous, and are frequently zoned in composition, temperature, and/or water content. They are typically stored in shallow crustal magma reservoirs (~ 2 to 5 km), which are maintained by mafic replenishment. Low melt viscosities (1 × 101.77 to 1 × 104.77 Pa s) facilitate two-phase flow, facilitating the formation of alkali-feldspar crystal mush. This mush may then contribute melt to an overlying melt lens via filter pressing or partial melting. We utilise a three stage model to account for the establishment, development, and termination of peralkaline magmatism in the ocean island magmatic systems of the Atlantic. We suggest that the overall control on peralkaline magmatism in the Atlantic is magma flux rate, which controls the stability of upper crustal magma reservoirs. The abundance of peralkaline magmas in the Atlantic suggests that their development must be a common, but not inevitable, stage in the evolution of ocean islands.